2019
DOI: 10.1002/ajmg.a.61160
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of a therapeutic effect of miransertib in a teenager with Proteus syndrome and ovarian carcinoma

Abstract: Proteus syndrome (PS) is an ultra‐rare disease characterized by progressive, disproportionate, segmental overgrowth caused by a somatic gain‐of‐function mutation p.Glu17Lys in the oncogene AKT1. The disease has high morbidity and mortality rates due to the increased risk for patients to develop cancer and progressive overgrowth. A teenage patient with severe PS phenotype developed a pelvic recurrence of low‐grade serous ovarian carcinoma (LGSOC). Taking into consideration, recent results of the use of AKT inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Treatment approaches in FCD/HME also include mTOR and PIK3CA inhibitors, as well as dietary measures in SLC35A2-related cases (21). Treatment with an AKT inhibitor has been reported in a female patient with Proteus syndrome and ovarian cancer (38).…”
Section: Treatmentmentioning
confidence: 99%
“…Treatment approaches in FCD/HME also include mTOR and PIK3CA inhibitors, as well as dietary measures in SLC35A2-related cases (21). Treatment with an AKT inhibitor has been reported in a female patient with Proteus syndrome and ovarian cancer (38).…”
Section: Treatmentmentioning
confidence: 99%
“…It is critical to note that his severe parenchymal lung disease was compounded by the restrictive lung disease due to vertebral and chest wall overgrowth and deformation. This combination of respiratory disease is difficult to treat, and may primarily be a manifestation that can best be avoided through primary drug treatment (Keppler-Noreuil et al 2019;Leoni et al 2019), rather than post-symptomatically.…”
Section: Discussionmentioning
confidence: 99%
“…80 Recently, Leoni et al reported a case of successful treatment with miransertib of a patient with Proteus syndrome that resulted in relapsed AKT1 E17K mutant ovarian cancer, and clinical and serological remission after 22 months of treatment. 81 Despite insufficient data to support clinical cancer therapy, promising reports of antitumour activity in patients harbouring AKT1 E17K mutations support the use of biomarker-driven strategies in further clinical development of this drug. Interestingly, Bougen-Zhukov et al observed that AKT3 was upregulated in the majority of E-cadherin-deficient GCs, and mouse-derived gastric organoids lacking tumour suppressor gene CDH1 were sensitive to the apoptotic effects of miransertib.…”
Section: Uprosertib (Gsk2141795)mentioning
confidence: 99%